2005
DOI: 10.1111/j.1467-6486.2005.00500.x
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Organizational Culture and Reshaping Capabilities on Change Implementation Success: The Mediating Role of Readiness for Change

Abstract: It was hypothesized that employees' perceptions of an organizational culture strong in human relations values and open systems values would be associated with heightened levels of readiness for change which, in turn, would be predictive of change implementation success. Similarly, it was predicted that reshaping capabilities would lead to change implementation success, via its effects on employees' perceptions of readiness for change. Using a temporal research design, these propositions were tested for 67 empl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
485
3
32

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 545 publications
(542 citation statements)
references
References 71 publications
22
485
3
32
Order By: Relevance
“…Similarly, our study found a negative correlation between market culture and control orientation of the organization and personal involvement in the organization. Results of our study are not entirely comparable to the research from developed countries (5,8,10,24,28). The results for physicians are comparable with similar research (24), but not the results for nurses -nurses in Slovenian hospitals found hierarchy to be the dominant current organizational culture, whereas nurses from other countries were mainly focused on flexibility and teamwork (24).…”
Section: Discussionsupporting
confidence: 78%
“…Similarly, our study found a negative correlation between market culture and control orientation of the organization and personal involvement in the organization. Results of our study are not entirely comparable to the research from developed countries (5,8,10,24,28). The results for physicians are comparable with similar research (24), but not the results for nurses -nurses in Slovenian hospitals found hierarchy to be the dominant current organizational culture, whereas nurses from other countries were mainly focused on flexibility and teamwork (24).…”
Section: Discussionsupporting
confidence: 78%
“…However, as Triandis (1996, p. 407) states, "almost all researchers agree that culture is reflected in shared cognitions [and] standard operating procedures." Our definition of culture in terms of attitudes and practices is consistent with and analogous to definitions that view culture in other terms, such as values, rituals, and codes (see Denison 1996;Deshpandé and Webster 1989;Gregory 1983;Jones, Jimmieson, and Griffiths 2005;Miles and Snow 1978;Rokeach 1973;Triandis 1994). As with labor and capital, culture can operate at both the national and the firm level.…”
Section: Drivers Of Radical Innovation In Firms Across Nationsmentioning
confidence: 77%
“…When organisational members have different cultures, beliefs and values, they, also, have different perceptions on various organizational changes [47]. In other words, organizational culture is a critical success factor for a project that requires significant changes [48]. Consequently, when the culture of an organisation is prone to change, ERP implementation is made quite easier.…”
Section: Amentioning
confidence: 99%